NUMERALIA BAHASA DAYAK MAANYAN (ANALISIS KONTRASTIF NUMERALIA BAHASA DAYAK MAANYAN DAN JAWA) (Numeral In Dayak Maanyan Language (A Contrastif Analysis On Numerals In Dayak Maanyan And Javanese Language)) - Dwiani Septiana (Balai Bahasa Sulawesi Selatan, 2017)
This study aims to describe the numeral grouping, words formation rules and word order in syntactic construction of Maanyan language and also describe the similarity and differences between Maanyan and Javanese language. This study conducted by using contrastive analysis theory and structural theory. This study is a library research. Data obtained by collecting the use of numeral in Maanyan language phrases and sentences. Data related with the structure of numeral in Javanese Language is taken from Tata Bahasa Jawa Mutakhir book. Research findings show that Numerals in Maanyan language are divided into two main groups according to their shape and various subgroups. The words formation was resulted from affixation, reduplication, and compounding. The numeral order in Maanyan language syntactic construction can be prenominal, post adverb or stand alone. There are three numerals that have the same form and meaning. The similar shape of numeral in both language are affix ka- to express the level in numeral, partial reduplication to express collective numeral and the addition of nasal sound in compound numeral.